PEMBERDAYAAN KADER DALAM DETEKSI DINI RISIKO TINGGI IBU HAMIL DI WILAYAH KERJA PUSKESMAS SUKORAME - Ira Titisari (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2019)
Every pregnancy will facing some severe emergency condition when giving a birth. The high risk condition could be detected by health practicioner or non health practicioner to skrinning or early detection when found some risk factor pro active on pregnant woman. The aim of this study was to increase the empowerment of kader in early detection of high risk of pregnant women at wilayah kerja puskesmas sukorame. This study was a quantitative research used pre-experimental designed onegroup pretest-posttest. The sample was selected by simple random sampling with 40 responden. The data were collected by quetionare.